Developing health practices of the grade one pupils of the Balara Elementary School, Quezon City - Madrid, Leyda (Longara) 1936- (1970)
The aim of the study is to expound on the proper development of health practices of the grade one pupils of Balara Elementary School, Quezon City. Specifically, it determines the least and the most practiced health behaviors of thirty six grade one pupils of the school, and the steps or measures that may be taken to correct the health behaviors that are undesirable and to develop those that are not yet established.
Thesis (M.A.T.Health Education)--University of the Philippines, Diliman.
Keywords: Balara Elementary School; Health education -- Quezon City